2002
DOI: 10.1177/104649640203300104
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Group Process Variables and Team Performance

Abstract: The efficacy of three group process variables-group potency, social cohesion, and teammember exchange-in explaining team performance was examined for 648 military officers working in 50 self-managed teams over a 5-week period. Team performance was assessed on two objective criteria (mental task performance and physical task performance) and one subjective criterion (commander team performance ratings). Each of the group process variables was related to at least one aspect of team performance. Of the three grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 28 publications
2
58
0
2
Order By: Relevance
“…A number of organizational studies applies social exchange theory to suggest that when individuals perceive support from their supervisors (i.e., leaders), they will reciprocate such supervisor support by engaging in behaviors that benefit the organization (Jordan et al 2002, Kim and Taylor 2001, Liden and Maslyn 1998. For example, in a study on perceived organizational support and leader-member exchange, Wayne et al (1997) have reported that individuals who experience high quality leader-member relationship are more willing to reciprocate through organizational citizenship behaviors.…”
Section: Perceived Leader Supportmentioning
confidence: 97%
“…A number of organizational studies applies social exchange theory to suggest that when individuals perceive support from their supervisors (i.e., leaders), they will reciprocate such supervisor support by engaging in behaviors that benefit the organization (Jordan et al 2002, Kim and Taylor 2001, Liden and Maslyn 1998. For example, in a study on perceived organizational support and leader-member exchange, Wayne et al (1997) have reported that individuals who experience high quality leader-member relationship are more willing to reciprocate through organizational citizenship behaviors.…”
Section: Perceived Leader Supportmentioning
confidence: 97%
“…La literatura sobre equips utilitza freqüentment de manera intercanviable els termes d'equip i de grup (Cohen i Bailey, 1997;De Dreu i Weingart, 2003;Guzzo i Dickson, 1996;West, Borrill i Unsworth, 1998;Jordan, Field, i Armenakis (2002). The).…”
Section: Delimitació Del Concepte D'equipunclassified
“…Promoting cooperative teamwork is one of the strategies for improving team efficacy (Jordan, Field, & Armenakis, 2002). Effective teams commonly share a sense of confidence that the team can collectively perform a task or mission well (Zaccaro, Blair, Peterson, & Zazanis, 1995).…”
Section: Cooperationmentioning
confidence: 99%